Seed hubs for East and Southern Africa: mobilizing knowledge and resources for resilient seed systems - Alliance of Bioversity International and CIAT; Wageningen Centre for Development Innovation (2021)
Given scarce resources for genetic resources evaluation networks and national breeding programs it makes sense for countries with common or complementary climate change and agricultural production challenges to pool their scarce resources in support of mutually satisfactory outcomes. It also make sense to look together for more resources and/or advocate for a reallocation of available resources. Sub-regional seed hubs or support/service unit(s) could address these needs, constituting an essential component of scaling strategies to mainstream the availability and use of biological/genetic diversity in seed systems for climate change adaptation. The hubs will be demand driven and provide intelligence and technical backstopping to farming communities, national and international research programmes, development actors, seed companies and policy decision-makers, on resilient seed systems tools, methods, information sources, data management, policy design and compliance with applicable regulations and agreements. This brief describes the proposed seed hubs in detail.